Determining receptivity and responsiveness for conservation: measurement, models and implications for strategy - Sherrod, Dixie, author; Vaske, Jerry, advisor; Donnelly, Maureen, advisor (Colorado State University. Libraries, 1999)
This dissertation is based on two articles. The first, Using the Stages of Change Framework to Measure Water Conservation Behavior, examines the stages of change construct as a framework to measure individual's beliefs about water resources, usage habits, receptivity and attitudinal responsiveness to conservation issues. The second, Using the Norm Activation Model to Describe Behavioral Change for Conservation investigates the feasibility of combining the constructs of the norm activation model within the stages of change framework to guide the development of strategic management action, advocacy and communication efforts. Data for the studies were collected using a simple random sample of 411 nonmetered homes in a Colorado municipality of 106,000. Homes within the sample were mailed an 8-page survey on two occasions, with a follow-up postcard sent 10 days after the first mailing. The response rate was 51 percent. Response rate was not considered a problem because support for conservation had been demonstrated in an earlier study (Maritz, 1991). The salience, and economic sensitivity, to impending water meter installation by state mandate was most likely attributable for the low response. Since our questions were about conservation, it was not likely that the low response accounted for non-response. In the first article, Using the Stages of Change Framework to Measure Water Conservation Behavior, a questionnaire operationalizes a behavioral change continuum ranging from no intention to change to adaptive coping for sustained change. It was comprised of four valid and reliable scales: precontemplation (α .63), contemplation (α .86), action (α .77) and maintenance (α .74). Results indicate that individuals can be located along the stages of change continuum. In the second article, Using the Norm Activation Model to Describe Behavioral Change for Conservation, the stages of change framework is successfully integrated with a complimentary model, norm activation. The constructs of norm activation: 1) awareness of consequences and 2) ascription of responsibility, provided insight onto the cognitions occurring within each of the three dimensions within the stages in change. By combining these theoretical approaches, a better understanding is gained of how behavior is changed, and predicted, for the conservation of natural resources, in this instance water. The integration of these paradigms implies that individuals can be encouraged within the change process to make incremental steps to adopt change for natural resource issues by the manipulation of normative variables. Implications for message design, communication planning and management action for natural resource communication and intervention programs are discussed.
Keywords: social psychology; mass media; recreation; environmental science; mass communications